Acute fibrinous and organizing pneumonia: A case report. Issue 8 (February 2019) - Wang, Yuanhui; Li, Yuwen; Wang, Qian; Zhang, Lili; Li, Jun; Zhu, Chuanlong
Abstract: Rationale: Acute fibrinous and organizing pneumonia (AFOP) is an uncommon type of acute lung injury associated with infection, connective tissue disorders, drug exposure, and hematologic malignancies. Patient concerns: A 53-year-old female presented with intermittent fever, chills, and dry cough since 10 days. Chest computed tomography scan showed multiple bilateral patchy infiltrates. PPD skin test was positive but tuberculosis antibody test and T-SPOT were negative. Diagnoses: Histologic examination revealed massive fibrinous exudation with organization within alveolar spaces and scattered neutrophilic infiltrates, which was consistent with AFOP. Interventions: This patient was treated with prednisolone therapy. Outcomes: Chest radiograph improvement and symptom improvement, including fever and respiratory symptoms, was observed after 2 week of oral prednisolone treatment. After 9-month of treatment, the patient was asymptomatic with stable disease and improved quality of life. Lessons: AFOP has unique pathologic manifestations; however, the condition is liable to be misdiagnosed as community-acquired pneumonia ortuberculosis. Antibiotics are ineffective, while some patients show good response to glucocorticoid therapy.